1983
DOI: 10.1099/0022-1317-64-7-1607
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition of Sonchus Yellow Net Virus

Abstract: SUMMARYSonchus yellow net virus (SYNV) contains approximately 18 ~ lipid composed of 62 ~ phospholipids, 319/o sterols and 7 ~o triglycerides. The polar phospholipids consist of phosphatidyl choline, phosphatidyl ethanolamine, phosphatidyl serine, phosphatidyl inositol and phosphatidyl glycerol respectively. The fatty acid composition of the individual phospholipids includes various ratios of palmitic, stearic, oleic, linoleic and linolenic acids. The neutral lipid fraction is composed primarily of free sterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Triterpenoids are the building blocks for sterols, which in algae are derived from the MVA pathway (Disch et al, 1998). These molecules constitute parts of cellular membranes (Hartmann, 1998), including viral envelopes (Selstam and Jackson, 1983). Therefore, the reduction in sterol abundance during viral infection can be a result of its consumption by newly produced viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenoids are the building blocks for sterols, which in algae are derived from the MVA pathway (Disch et al, 1998). These molecules constitute parts of cellular membranes (Hartmann, 1998), including viral envelopes (Selstam and Jackson, 1983). Therefore, the reduction in sterol abundance during viral infection can be a result of its consumption by newly produced viruses.…”
Section: Discussionmentioning
confidence: 99%
“…After we determined the basic physiochemical properties of SYNV ( 17), more detailed analyses of SYNV structural proteins (18) and lipids (19) were conducted for comparisons with other rhabdoviruses. To determine whether SYNV is a negative-strand virus, I initiated RNA-dependent RNA polymerase studies similar to those reported previously for LNYV by Richard Francki but was unable to confirm polymerase activity in purified SYNV or PYDV.…”
Section: On My Own At Purduementioning
confidence: 99%
“…Sonchus yellow net virus (SYNV), a plant rhabdovirus, has bacilliform particles (Jackson andChristie, 1977, 1979) which consist of a distinctive nucleocapsid core and an envelope (Selstam and Jackson, 1983). Physicochemical studies of the virus and analysis of RNAs from infected plants reveal that the genome consists of a minus sense RNA approximately 13,000 nucleotides (nt) long (Milner and Jackson, 1979;Rezaian et a/., 1983).…”
Section: Introductionmentioning
confidence: 99%